Parameter estimation of HFMD infection in Malaysia with SIR model - Hanis Nasir; Fuaada Mohd Siam (Annals of Mathematical Modeling, 2023)
Hand, foot and mouth disease (HFMD) is a mildly infectious disease that happens to children due to low body immunity against viruses. In this paper, a simple SIR model is employed to represent the dynamics of HFMD in Malaysia. A weekly reported data of HFMD infection from week-1 of 2017 to week-36 of 2018 is used in the mathematical analysis. The procedure of parameter estimation is implemented in order to identify the parameter of the SIR model that fits the model with the reported data. The fminsearchbnd routine is used to minimize the objective function, which is the sum of absolute error minimization. By the Chi-squared test, the estimated parameters are reasonable. Based on the average value of the basic reproduction number R0, HFMD infection will remain to exist in the population under the current condition. Overall, this finding may be useful for public health personnel to reduce disease infection risk by planning more effective prevention strategies.